Shared polygenic risk and causal inferences in amyotrophic lateral sclerosis. Issue 4 (13th March 2019) - Bandres‐Ciga, Sara; Noyce, Alastair J.; Hemani, Gibran; Nicolas, Aude; Calvo, Andrea; Mora, Gabriele; ,; ,; Tienari, Pentti J.; Stone, David J.; Nalls, Mike A.; Singleton, Andrew B.; et al.
Abstract : Objective: To identify shared polygenic risk and causal associations in amyotrophic lateral sclerosis (ALS). Methods: Linkage disequilibrium score regression and Mendelian randomization were applied in a large‐scale, data‐driven manner to explore genetic correlations and causal relationships between >700 phenotypic traits and ALS. Exposures consisted of publicly available genome‐wide association studies (GWASes) summary statistics from MR Base and LD‐hub . The outcome data came from the recently published ALS GWAS involving 20, 806 cases and 59, 804 controls. Multivariate analyses, genetic risk profiling, and Bayesian colocalization analyses were also performed. Results: We have shown, by linkage disequilibrium score regression, that ALS shares polygenic risk genetic factors with a number of traits and conditions, including positive correlations with smoking status and moderate levels of physical activity, and negative correlations with higher cognitive performance, higher educational attainment, and light levels of physical activity. Using Mendelian randomization, we found evidence that hyperlipidemia is a causal risk factor for ALS and localized putative functional signals within loci of interest. Interpretation: Here, we have developed a public resource (https://lng-nia.shinyapps.io/mrshiny ) which we hope will become a valuable tool for the ALS community, and that will be expanded and updated as new data become available. Shared polygenic risk exists between ALS and educational attainment, physical activity, smoking, and tenseness/restlessness. We also found evidence that elevated low‐desnity lipoprotein cholesterol is a causal risk factor for ALS. Future randomized controlled trials should be considered as a proof of causality. Ann Neurol 2019;85:470–481